Mathematical Modeling of Thermal Drying of Facultative Pond Sludge - Leite, Luan de Souza [UNESP]; Matsumoto, Tsunao [UNESP]; Albertin, Liliane Lazzari [UNESP] (Asce-amer Soc Civil Engineers, 2018)
This study investigated the sludge drying from a facultative pond in a dryer that employs two dehydration methods: thermal drying by infrared lamps and convective drying. For the tests, three thicknesses of sludge were used (10, 25, and 50mm) and different drying times (6 and 12h). From the results, the data obtained was compatible with the adjustment of eight mathematical models utilized for thin layers (Newton, Henderson and Pabis, Page, two-term Wang and Singh, logarithmic, diffusion approximation, and Midilli) by four statistical parameters: determination coefficient (R2), reduced chi-square (2), root mean square error (RMSE), and mean relative deviation modulus (P). Even though this work used sludge layers greater than those found in the literature, the results for any mathematical model were satisfactory (R2>0.9931). The Midilli model was the best in describing the drying behavior of the three thicknesses (R2>0.9996). These results support the use of thin layer models for facultative pond sludge drying, and it could be a practical tool for dryer projects using large thickness.
Keywords: Sludge drying; Sewage sludge; Facultative pond sludge; Dehydration methods; Midilli model; Thermal drying